THE STUDY OF TEACHERS’ TEACHING-LEARNING BEHAVIOR IN THE EFL CLASSROOM BASED ON FUNDAMENTAL INTERPERSONAL RELATIONS ORIENTATION THEORY - Casimirus Andi Fenanlampir (Universitas Musamus, Merauke, Papua, 2016)
The study aims to identify and describe forms and patterns of teachers’ basic behavior in teaching-learning processes based on Fundamental Interpersonal Relations Orientation (F.I.R.O.) theory. The study is descriptive qualitative in which its sample consists of four permanent teachers of English Education Department who have at least five years of experience in teaching-learning processes. FIRO-Behavior analysis was used as the techniques of data analysis in order to investigate teachers’ basic behavior in the classroom. The results indicate that teachers’ basic behavior tends to be more dominant which is categorized in inclusion as social, control as democratic, and openness as personal in establishing interpersonal relationships with students. Teachers tend to act as clarifiers and directors so that the given input and feedback in supporting students through language exposure and learning experiences were not optimal.